THE EFFECT OF PROFITABILITY, LIQUIDITY, COMPANY SIZE, AND SALES GROWTH ON CAPITAL STRUCTURE IN CONSUMER NON-CYCLICALS COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2021-2023 PERIOD - Patricia, Selvia Putri; Dewi, Sofia Prima (International Journal of Application on Economics and Business, 2025)
The optimal capital structure configuration becomes a crucial determinant in ensuring the survival and long-term growth of a business entity. The study endeavors to furnish empirical substantiation concering the effect of profitability, liquidity, company size, and sales growth on capital structure. The research employs a quantitative approach with a purposive sampling technique, using sample of 34 companies listed on the Indonesia Stock Exchange during the periods of 2021, 2022, and 2023. Data were processed using E-Views version 12 to test the hypotheses. The findings of this study suggest that profitability does not negatively influence the capital structure. Company size and sales growth do not positively influence the capital structure, while liquidity has a negatively influence the capital structure. The implications of this research for companies indicate that they must carefully consider the factors identified in this research when formulating an optimal capital structure, in order to support sustainable growth and effectively manage financial risks. For investors, the findings provide valuable insights into analyzing a company’s capital structure as a foundation for more informed investment decision-making. Furthermore, future research could broaden its scope by exploring other external factors that may influence capital structure decisions.